2016
DOI: 10.3389/fmicb.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

A Chlorhexidine- Agar Plate Culture Medium Protocol to Complement Standard Broth Culture of Mycobacterium tuberculosis

Abstract: The culture of Mycobacterium tuberculosis using parallel inoculation of a solid culture medium and a liquid broth provides the gold standard for the diagnosis of tuberculosis. Here, we evaluated a chlorhexidine decontamination-MOD9 solid medium protocol versus the standard NALC-NaOH-Bactec 960 MGIT protocol for the diagnosis of pulmonary tuberculosis by culture. Three-hundred clinical specimens comprising 193 sputa, 30 bronchial aspirates, 10 broncho-alveolar lavages, 47 stools, and 20 urines were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…El Khechine et al replaced NaOH decontamination with 0.25% chlorhexidine in their laboratory handling of stool samples ( 19 , 38 ), citing unpublished data of improved recovery versus contamination compared to NaOH ( 19 ). Chlorhexidine is inactive against mycobacteria and may increase the recovery of M. tuberculosis ( 39 , 40 ). The sensitivity of stool culture in the study by El Khechine is the highest reported for the diagnosis of PTB at 54% ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…El Khechine et al replaced NaOH decontamination with 0.25% chlorhexidine in their laboratory handling of stool samples ( 19 , 38 ), citing unpublished data of improved recovery versus contamination compared to NaOH ( 19 ). Chlorhexidine is inactive against mycobacteria and may increase the recovery of M. tuberculosis ( 39 , 40 ). The sensitivity of stool culture in the study by El Khechine is the highest reported for the diagnosis of PTB at 54% ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then crushed using a piston pellet in 2 mL Eppendorf-tubes containing 1mL of sterile PBS and filtered through a 5μm filter to remove the debris. A 1mL-volume of each homogenate was decontaminated with 1% chlorhexidine and then 100 μL were cultured on MOD9 medium (11).…”
Section: Methodsmentioning
confidence: 99%
“…In the search of reducing MTB culture time, which takes more than 2 weeks on conventional media, we set up a step-by-step protocol with a new MOD4 media (blood and egg lecithin) in microaerophilic atmosphere or ascorbic acid supplement and autofluorescent detection, allowing a marked reduction of culture time, with, in some occasion, rifampin susceptibility testing available after 72 hours of growth [90] . On the basis of this knowledge, we developed a novel solid medium for culturing MTB isolates from clinical specimens that we named MOD9, a blood-free derivative of MOD4; we showed that the detection time was significantly shorter compared to conventional Lowenstein medium [97] and standard culture broth [98] .…”
Section: New Antimalarial Drugsmentioning
confidence: 99%